Acometimento neurológico no Covid longo: caracterização clínica e epidemiológica em uma amostra ambulatorial - Oliveira, Danilo Nunes (2023)
The COVID-19 is a respiratory viral infection that can have severe outcomes. Neurological manifestations have already been described in the acute phase of the disease, with the most serious being encephalopathy, stroke, and seizures. Long COVID occurs after the initial phase, with symptoms such as cognitive dysfunction, headache, anosmia, and others. This study analyzed the association between COVID-19 infection and neurological manifestations in a cohort of outpatient patients. It included 221 patients who were seen between July 2020 and May 2022 and who presented persistent neurological complaints after the infection. The patients underwent clinical, neurological, and APOE gene genotyping evaluations. The results showed that olfactory dysfunction was one of the most common symptoms during the acute phase of the infection. In the Long COVID, the most common symptoms were cognitive impairment (57.9%), headache (31.2%), and olfactory dysfunction (29.4%), with diagnoses of polyneuropathy (4%), stroke (2.7%), and dementia (2.7%). The most frequent APOE genotype in the evaluated population was E3/E3, followed by E3/E4. The presence of the E4 allele of the APOE gene was associated with a lower frequency of olfactory dysfunction (15.1% vs. 30.1%, p=0.035) and a higher incidence of cognitive impairment post-COVID (30.8% vs. 16.4%, p=0.038). The results suggest that neurological manifestations are common in patients with COVID-19, both during the acute infection and after recovery. Olfactory dysfunction is one of the most common symptoms and can persist for weeks or months after the infection. In the literature, anosmia has been a predictor of a favorable respiratory outcome. The E4 allele, already well-established as a risk factor for Alzheimer's disease and severe respiratory manifestations in COVID-19, may be associated with greater cognitive impairment in the Long COVID. Further research is needed to fully understand the causes and consequences of these neurological manifestations associated with COVID-19.